Medicinal potential of the genera furcraea and agave (2014)
Introduction: the genera Furcraea and Agave comprise a large number of xerophytic plants which are exploited mainly in Mexico, Colombia and Brazil to obtain beverages, twine, sacks, handicrafts, animal feed, pharmaceuticals, biomass, construction reinforcements, fertilizers and cultivation substratum, among other direct uses. Their extracts contain a great variety of chemical compounds, many of which have potential applications in the treatment of diseases such as cancer. Among such compounds are saponins, hecogenins, fructans, cellulose and hemicellulose. Objectives: explore the information published about the genera Furcraea and Agave and their medicinal and agroindustrial properties, and infer their future research and exploitation possibilities. Methods: a bibliographic search was conducted in the databases ScienceDirect, SpringerLink, AcademicSearch Complete (EBSCO) and Redalyc of documents published from 1995 to 2012. A selection was made of papers including the chemical characterization of the plants, their alternative uses and the methods of chemical analysis employed. Results: a presentation is provided of the information gathered about 4 species of the genus Furcraea and 9 of the genus Agave. Some of the species analyzed contain saponins, which are chemical compounds potentially useful in the treatment of cancer. A report is included of the presence of free carbohydrates, such as glucose and fructose, and polymeric carbohydrates like fructanes. The latter are classified as prebiotic. Cellulose, hemicellulose and lignin, which constitute the fiber mainly of leaves, may be used as chelating agents of biological origin. Conclusions: plants of the genera Furcraea and Agave, considered in this review, contain chemical substances potentially useful in a variety of medical and industrial fields, though some species have not been studied exhaustively. © 2014, Editorial Ciencias Medicas. All rights reserved.